2019
DOI: 10.1111/and.13359
|View full text |Cite
|
Sign up to set email alerts
|

Sperm parameters quality and reproductive effects of methanolic extract ofAlchornea cordifolialeaves on senescent male rats

Abstract: The effect of the methanolic extract of Alchornea cordifolia leaves on the fertility of senescent male rats was assessed in this study. 40 rats received daily distilled water, testosterone, 200 and 400 mg/kg of extract of Alchornea cordifolia. The reproductive organs weight, the gonadotropins, testosterone and cholesterol level, the sperm parameters, histology of the testes and epididymis were assessed. The weight of testes and prostate (400 mg/kg) significantly increased (p < 0.05) as well as the level of FHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The Ghrelin receptor was found mostly in Leydig cells and to a lesser amount in Sertoli cells, confirming GRE function in spermatogenesis regulation. Furthermore, research have revealed that GRE delays the beginning of puberty in male rats and modulates the proliferation of Leydig cells (10). Chronic Ghrelin treatment improves the antioxidant defense mechanism in the rat testis by increasing GPx activity and lowering MDA levels, according to evidence (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ghrelin receptor was found mostly in Leydig cells and to a lesser amount in Sertoli cells, confirming GRE function in spermatogenesis regulation. Furthermore, research have revealed that GRE delays the beginning of puberty in male rats and modulates the proliferation of Leydig cells (10). Chronic Ghrelin treatment improves the antioxidant defense mechanism in the rat testis by increasing GPx activity and lowering MDA levels, according to evidence (30).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin suppressed mRNA expression of the gene encoding stem cell factor (SCF), a critical signal for germ cell generation and a possible regulator of Leydig cell development, in adult rats (5). Chronic Ghrelin therapy improves the antioxidant defense mechanism in the rat testis by increasing glutathione peroxidase activity (GPX) and lowering malondialdehyde (MDA) levels (10). In this study we evaluated the effect of Ghrelin on sperm analysis and the antioxidant system.…”
Section: Introductionmentioning
confidence: 99%
“…Using a surgical microscissor, the left caudal epididymis was submerged in 2 ml of phosphate-buffered saline and sliced into roughly 200 pieces to liberate the spermatozoa from the epididymal tubules measured (Ngaha Njila et al, 2019). The epididymal semen suspension was right away kept at 37°C for future investigation.…”
Section: Evaluation Of Sperm Qualitymentioning
confidence: 99%
“…Alchornea cordifolia leaves remain effective in the treatment of male fertility problems. Studies conducted by Ajibade and Olayemi (2015) and Ngaha-Njila et al (2019) have shown that the methanoic extract of Alchornea cordifolia leaves improves male fertility and sperm quality, respectively. Nevertheless, few studies have been done with the aqueous extract.…”
Section: Introductionmentioning
confidence: 99%